2021
DOI: 10.1177/14767503211004707
|View full text |Cite
|
Sign up to set email alerts
|

Using a virtual platform for an asynchronous co-operative inquiry

Abstract: A participatory action research (PAR) study using co-operative inquiry methods was employed to examine the topic ‘spirituality and childbirth’. Co-operative inquiry (CI) reclaims the right of co-researchers to create knowledge from their own lived experience, an approach that works ‘with’ rather than ‘on’ people, valuing individual contributions. Traditionally, CI has been organised synchronously in the same physical location. However, with current events and need for greater global collaboration for divergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…These factors cultivated the democratic participation, one-and-many perception, and multiple ways of knowing determining a CIs trustworthiness. CI groups also highlighted the many challenges of asynchronous engagement, including the potential for unequal participation (Astle, 2001;Duenkel et al, 2014), feelings of isolation (Hanlin-Rowney et al, 2006), and loss of embodied emotional cues (Crowther et al, 2021). These decreased the interpersonal connections and reflective capacity of groups.…”
Section: The Potentials and Challenges Of Mediating CI Processes Thro...mentioning
confidence: 99%
See 4 more Smart Citations
“…These factors cultivated the democratic participation, one-and-many perception, and multiple ways of knowing determining a CIs trustworthiness. CI groups also highlighted the many challenges of asynchronous engagement, including the potential for unequal participation (Astle, 2001;Duenkel et al, 2014), feelings of isolation (Hanlin-Rowney et al, 2006), and loss of embodied emotional cues (Crowther et al, 2021). These decreased the interpersonal connections and reflective capacity of groups.…”
Section: The Potentials and Challenges Of Mediating CI Processes Thro...mentioning
confidence: 99%
“…CI researchers experienced similar frustrations when attempting to conduct member checks or involve participants in asynchronous data analysis (Howell, 2020;Moreira-Ramirez, 2020). The analysis phase benefitted from moving to synchronous gatherings (Crowther et al, 2021). Whitaker et al (2022), however, reported success using Google Docs as a kind of less individually segmented discussion board to engage participants in a continuous dialogue in a single document between meetings and across CI phases.…”
Section: The Potentials and Challenges Of Mediating CI Processes Thro...mentioning
confidence: 99%
See 3 more Smart Citations